Institutionalization of Islamic Law in Indonesia - Tahmid, Khairuddin; Fautanu, Idzan (al-'adalah, 2021)
This article discusses the institutionalization of Islamic law into national law in Indonesia. The aim is to analyze the possibility of incorporating Islamic Law into the national legal system. This desire is logical, considering that Muslims in Indonesia occupies the majority position (85%) and the community requires appropriate regulations sourced from the teachings of their religion. Based on the results of the 1979/80 BPHN legal review seminar, there are at least 3 (three) main things that could be done, namely; (1) making Islamic law one of the ingredients in the preparation of national law, (2) reviewing and updating national legal products originating from colonial law that is not following the elements of Islamic law. (3) coordinating new regulations which contain Islamic legal norms. This study finds the fact that not all provisions of Islamic law can be incorporated into national law. Only provisions of a civil nature and which are truly correlated with public order (public interest) can be adopted. Apart from that, the law is not only a legal product but also a political product. In other words, the configuration of legal politics in Indonesia shows a very close relationship with the political realm. Therefore, it is necessary to have a strong synergy between Muslim intellectuals and political actors.Keywords: Islamic law, legal politics in Indonesia, political configuration.